Pertumbuhan Tanaman Vanili (Vanilla planifolia) dalam Polybag pada Beberapa Kombinasi Media Tanam dan Frekuensi Penyiraman Menggunakan Teknologi Irigasi Tetes - Jamaludin, Jamaludin; Ranchiano, M. Gary (Jurnal Agro Industri Perkebunan, 2021)
The study aimed to find the media composition and watering frequency through drip irrigation technology, which is appropriate to support the growth of vanilla plants in polybags. The research was conducted in the STIPER Dharma Wacana Metro experimental garden from April to July 2020. The first factor is the composition of the planting medium, namely soil + manure, soil + manure + rice husks, soil + manure + sand, and soil + manure + cocopeat. The second factor is watering frequency, namely 1, 2, and 3 times a day. Each treatment was repeated three times. The variables observed included plant height (cm), number of leaves (strands), shoot fresh weight (g), root fresh weight (g), and biomass dry weight (g). The use of mixed media of soil, manure, and cocopeat is the best media composition by producing a root wet weight of 8.0 g and a dry weight of 7.2 g. The frequency of watering three times a day resulted in the best height of vanilla plants being 51.8 cm compared to the frequency of watering once and twice a day. There was no interaction between the composition of the growing media and the frequency of watering on vanilla plants growth in polybags.